Epistemología, caos y enseñanza de las ciencias - Luffiego García, Máximo; Bastida, M. F.; Ramos, F.; Soto, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
In this article it is maintained that modern science is going through a critical period where its epistemological assumptions and the use of a parcelling and reductionist methodology are questioned. This will surely have important implications in the teaching of the sciences, perhaps because the world today demands above all an epistemological change in the people who, within a few years, will occuppy the posts in the production and reproduction of scientific and technical knowledge